2017
DOI: 10.1002/aoc.3986
|View full text |Cite
|
Sign up to set email alerts
|

Excellent alkene epoxidation catalytic activity of macrocyclic‐based complex of dioxo‐Mo(VI) on supermagnetic separable nanocatalyst

Abstract: A phenoxybutane-based Schiff base complex of cis-dioxo-Mo(VI) was supported on paramagnetic nanoparticles and characterized using powder Xray diffraction, infrared, diffuse reflectance and atomic absorption spectroscopies, scanning and transmission electron microscopies and vibrating sample magnetometry. The separable nanocatalyst was tested for the selective epoxidation of cyclohexene, cyclooctene, styrene, indene, α-pinene, 1-octene, 1-heptene, 1-dodecene and trans-stilbene using tert-butyl hydroperoxide (80… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 55 publications
(84 reference statements)
1
7
0
Order By: Relevance
“…According to our previous works on the catalytic activity of d‐block Schiff base complexes, a MnFe] 2 O 4 supported Mo(VI) Schiff base complex, MnFe 2 O 4 ‐Mo(VI), derived from 1,3‐bis(4‐bromo‐2‐carboxyaldehyde phenoxy)propane has been developed in the presented work (Figure ). The novel heterogeneous catalyst was tested for its ability to oxidize olefins and sulfides selectively into epoxides and sulfoxides in green solvent‐less condition.…”
Section: Introductionsupporting
confidence: 51%
See 2 more Smart Citations
“…According to our previous works on the catalytic activity of d‐block Schiff base complexes, a MnFe] 2 O 4 supported Mo(VI) Schiff base complex, MnFe 2 O 4 ‐Mo(VI), derived from 1,3‐bis(4‐bromo‐2‐carboxyaldehyde phenoxy)propane has been developed in the presented work (Figure ). The novel heterogeneous catalyst was tested for its ability to oxidize olefins and sulfides selectively into epoxides and sulfoxides in green solvent‐less condition.…”
Section: Introductionsupporting
confidence: 51%
“…Transition metal complexes are widely used as catalysts for production of important organic compounds Mo(VI) complexes have in particular found interest for the oxidation of olefins and sulfides into epoxides and sulfoxides to provid access to industrially important compounds, surfactants, intermediates, drug, antifungal agents and epoxy resins . Homogeneous catalysts are mainly used for these chemical transformations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such structure is very efficient for low temperature epoxidation, leading to conversion and selectivity [cyclooctene (Y=100 %), styrene (Y=2.4 %), limonene (Y=75.2 %), Table S1, #94‐98]. Payami et al . reported macrocyclic‐based complex of dioxo‐Mo (VI) on supermagnetic separable nanocatalyst which show good performances for oxidation of cyclohexene (Y=100 %), cyclooctene (Y=100 %), 1‐heptene (Y=86 %), 1‐octene (Y=86 %), 1‐dodecene (Y=87 %), styrene (Y=18 %), Table S1, #99–104.…”
Section: Mo‐based Catalystsmentioning
confidence: 99%
“…Such structure is very efficient for low temperature epoxidation, leading to conversion and selectivity [cyclooctene Table S1, #94-98]. Payami et al [51] reported macrocyclic-based complex of dioxo-Mo (VI) on supermagnetic separable nanocatalyst which show good performances for oxidation of Table S1, #99-104.…”
Section: P E R S O N a L A C C O U N T T H E C H E M I C A L R E C O R Dmentioning
confidence: 99%